Oxford handbook of head and neck anatomy - van Gijn, Daniel (New York : Oxford University Press, 2022)
"The human skull is the skeleton of the head and is considered along with the mandible. It consists of paired bones and un-paired midline bones that contribute to the muscular attachments for mastication and facial expression, a bony foundation for the upper aerodigestive tract and support and housing for those structures susceptible to trauma - the special sensory organs and brain"--